PELATIHAN MEDIA INTERAKTIF BERBASIS GAME MENGGUNAKAN APLIKASI WORDWALL UNTUK MENINGKATKAN KETERAMPILAN GURU SEKOLAH DASAR - Rahmatih, Aisa Nikmah; Fauzi, Asri; Ermiana, Ida; Suranti, Ni Made Yeni; Handika, Ilham (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2024)
One way to design interactive learning is by utilising digital applications or websites that provide media creation services. By utilising sites that provide digital-based media creation services, students' interest in participating in the learning process increases and the teaching and learning process becomes more interesting. One platform that offers interactive game-based media creation is the Wordwall platform. The Wordwall educational game is a website-based application that can be used as a learning medium with interactive game features. This training was chosen because the Wordwall platform has been proven to increase student interest, motivation, and learning outcomes. Thus, the community service team held training on creating interactive game-based media using the Wordwall platform to improve the digital skills and abilities of elementary school teachers. The purpose of this training is to train teachers in developing interactive game-based media using the Wordwall application. The target in this study was 14 teachers at SDN 15 Cakranegara. The stages of implementing community service activities are the preparation stage, the implementation stage, and the evaluation stage. The results of this community service are that teachers are very enthusiastic about this interactive learning media development training because of the need for teachers to improve the learning process in the classroom. Overall, interactive game-based media training using the Wordwall application is the right step in improving the skills of elementary school teachers in creating innovative and effective learning media. With the right support and guidance, teachers can leverage this technology to improve the quality of learning, which will ultimately have a positive impact on student learning outcomes.